The Influence of Leader Member Exchange and Perceived Organizational Support on Organizational Citizenship Behavior - Ramadhan, Aditya; Riyanto, Setyo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Objective -The aim of the research is to analyze Leader Member Exchange and Perceived Organizational Support towards Organizational Citizenship Behavior mediated by Employee Engagement at the BPJS Health Head Office. Methodology/approach –Using quantitative methods and conducting surveys on employees, after that SEM analysis is used to model causal relationships between complex variables and test existing theories or hypotheses. Meanwhile, researchers used the Partial Least Square (smart-PLS) application version 3.2.9 PLS to process the data. results found that Leader Member Exchange had a significant positive effect on Employee Engagement and Organizational Citizenship Behavior. Perceived Organizational Support has a significant positive effect on Employee Engagement and Organizational Citizenship Behavior. Leader Member Exchange and Perceived Organizational Support also have a significant effect on Organizational Citizenship Behavior through Employee Engagement as a Mediating Variable.